A dynamic analysis of the aluminum titanate (Al₂TiO₅) reaction-sintering from alumina and titania, properties and effect of alumina particle size - Violini, María Agustina (2021)
Aluminum titanate Al₂TiO₅ materials were successfully processed from different fine commercial powders and characterized. Particularly, two calcined aluminas were compared through a multitechnique approach including differential thermal analysis and dilatometry together with structural, microestructural, and mechanical characterization. This allowed the description of all the thermochemical processes during thermal treatment. Developed phases were established. Relatively dense ceramics were obtained, and complex microstructures were described with interlocked grains and an interconnected microcrack matrix that do not jeopardize the material integrity. Multistep sintering and reaction sintering processes were observed in both samples. The first stage consists of the sintering of the starting powders (alumina and titania). A second sintering stage of the starting powders was observed for both samples as well. Once advanced, the second one is overlapped with Al₂TiO₅ formation that starts at 1380 °C and finishes at 1440 °C. They affect crack development and, in consequence, the thermal behavior. The lower alumina particle size enhances the sintering and reaction advance processes. In the technological temperature range (room temperature—1000 °C), low or even negative thermal expansion behaviors were observed in the developed materials. This, together with the mechanical behavior, encourages structural applications with high thermomechanical solicitations of Al₂TiO₅ based materials.